Delivering nitric oxide with poly(n-butyl methacrylate) films doped with S-nitroso-N-acetylpenicillamine. (16th July 2021) - Zhou, Yang; Wu, Peixuan; Wu, Jianfeng; Doverspike, Joshua C.; Zhang, Qi; Shao, Jinyu; Xi, Chuanwu; Liu, Yuanyuan; Meyerhoff, Mark E.
Abstract: Controllable delivery of nitric oxide (NO) platforms have attracted considerable attention for biomedical/therapeutic applications. Poly( n -butyl methacrylate) is one of the most widely explored biomedical materials as a primer and is used in manufacturing the commercial XIENCE family of coronary stents. Herein we report the preparation of NO-releasing poly( n -butyl methacrylate) (PBMA) films via incorporation of S -nitroso- N -acetylpenicillamine (SNAP) within, and explore the NO-releasing profiles of such films under physiological conditions. Specifically, the total NO-release time of PBMA films doped with SNAP can reach up to 75 d, and the total leaching of SNAP is extremely low (~2.2%, based on HPLC-MS measurements). The surface morphology of SNAP-doped PBMA films indicates the formation of needle-like crystalline SNAP particles, which is further confirmed by the PXRD data. Based on element mapping, SNAP is found to be homogenously distributed within the PBMA polymer phase. Moreover, the antimicrobial and anti-biofilm properties of the NO-releasing PBMA polymer films are demonstrated using E. coli, P. aeruginosa, S. aureus, and S. epidermidis bacterial strains over 7 d periods. These results suggest that the controllable release of NO using PBMA films could be useful for therapeutic or biomedical device applications. Moreover, the corresponding data would also contribute to the exploration of the controllable drug release property using PBMA as the polymer matrix during the manufacture of biomedical stents. Graphical abstract: Image 1 Highlights: Nitric oxide release poly( n -butyl methacrylate) polymer films were fabricated. Nitric oxide release time can reach up to 75 d. Extremely low chemical leaching (~2.2%) was obtained. The fabricated films demonstrated antimicrobial and anti-biofilm properties.